Implementasi Sistem Informasi Pelayanan Kesehatan Pada Klinik Smart Medica - Rahayu Amalia; Nurul Huda (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
The clinic is one of the public services engaged in the health sector which is inseparable from the development of information technology. Smart Medica Clinic in data processing is still done manually where information about the Smart Medica clinic is difficult to obtain, such as information about the doctor and also the doctor's schedule on duty while the Smart Medica clinic is one of the largest clinics in Sekayu Regency and also already famous and has many patients. With this situation, web-based information systems are built so that services to the community can be comprehensive and the Smart Medica Clinic can provide information that is needed by patients up to date and also patient satisfaction is fulfilled. This information system was built using the WaterFall method, using the PHP programming language and the My Sql database.